Analysis of Technical Abilities And Physical Condition for Women’s Basketball Athletes of Bandung - Masayu Rizka Risjanna; Alen Rismayadi; Dadan Mulyana; Widi Kusumah; Yudi Nurcahya; Rafdlal Saeful Bakhri (JUARA : Jurnal Olahraga, 2022)
Several factors, such as the readiness of technical abilities and physical condition, are basic things that are important to the development and achievement of basketball athletes. This research aims to describe the results of the analysis of the technical abilities and physical condition of female basketball athletes. The method used in this research is a descriptive method using a quantitative approach with a correlational type of research to examine the relationship between technical abilities and physical condition variables on performance. This research was conducted in 2022 with the population of female basketball athletes of Bandung who will compete in the multievent PORPROV basketball Game in 2022. The instrument in this research used five technical skill test items, namely the passing skill test; shooting skills test; Under-ring test; lay-up skills; Illinois Agility Dribbling Test, and seven physical condition test items, namely the Wall Sit Test (Limb Muscle Endurance); 20-meter Sprint Test (Speed); Illinois Agility Test, Vertical Jump Test, Bleep Test, Flexibility Test. In the Pearson correlation output, there is a correlation that shows the relationship between skill technique and physical condition with the performance of Bandung women's basketball players, with a significant contribution from technical abilities and physical condition to the player's performance was 48.2%.